2015
DOI: 10.1021/acs.chemmater.5b00411
|View full text |Cite
|
Sign up to set email alerts
|

Structural Investigation of Graphitic Carbon Nitride via XRD and Neutron Diffraction

Abstract: Graphitic carbon nitride (g-C 3 N 4 ) has, since 2009, attracted great attention for its activity as a visible light-active photocatalyst for hydrogen evolution. Since it was synthesized in 1834, g-C 3 N 4 has been extensively studied both catalytically and structurally. While its 2D structure seems to have been solved, its 3D crystal structure has not yet been confirmed. This study attempts to solve the 3D structure of graphitic carbon nitride by mean of x-ray diffraction and of neutron scattering. Initially,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
436
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 658 publications
(507 citation statements)
references
References 27 publications
40
436
1
2
Order By: Relevance
“…The asprepared PCN sample often has a C/N ratio of around 0.67, and ∼1 wt% H. Therefore, the structure of this carbon nitride is best represented by the melon model. [15][16][17][18][19] . This model has compositional formula C 6 N 9 H 3 .…”
Section: Polymeric Carbon Nitridesmentioning
confidence: 99%
See 1 more Smart Citation
“…The asprepared PCN sample often has a C/N ratio of around 0.67, and ∼1 wt% H. Therefore, the structure of this carbon nitride is best represented by the melon model. [15][16][17][18][19] . This model has compositional formula C 6 N 9 H 3 .…”
Section: Polymeric Carbon Nitridesmentioning
confidence: 99%
“…1a contains the XRD patterns of samples prepared at temperatures from 500 to 700 • C. These samples show characteristic patterns of melon. 15,17,18 Two main reflections at ∼ 13 • and ∼ 27.5 • are assigned to intralayer periodicity (210) and interlayer periodicity (001), respectively. Transmission Electron Microscopy (TEM) images show that CN700 has a plate-like morphology ( Fig.…”
Section: Structural Featuresmentioning
confidence: 99%
“…22,[49][50][51] This synthesis procedure results in polymeric materials that have a limiting composition near that of Liebig's melon, with structures derived from ribbon-like elements formed by linked chains of heptazine (C 6 N 7 ) units. [20][21][22]49,50,52 Among the amorphous materials produced at higher temperatures, some elements containing more highly condensed graphite-like domains may be present, but this has not been proved experimentally. It might be expected that the end result from continued elimination of NH 3 would cause formation of fully graphitic g-C 3 N 4 layers based on linked polyheptazine units (Fig.…”
mentioning
confidence: 99%
“…Since hep002 / tri002 decreased with heating duration (Figure 5(c)), the layered structure is considered to consist mainly of s-triazine-based network. However, a first-principle calculation [3] reported that heptazine-based carbon nitride is thermodynamically more stable than the s-triazine-based one, and some experimental studies also showed the production of the heptazinebased carbon nitride under high temperatures [13,42,44,45]. Thomas et al [43] reported that the condensation of striazine ring unit to heptazine ring unit occurred at above 390 ∘ C through the elimination of ammonia.…”
Section: Resultsmentioning
confidence: 99%